Undifferentiated uterine sarcoma : experience of a single center - Hua Yuan; Tonghui Wang; Ning Li; Hongwen Yao (World Journal of Surgical Oncology)
Abstract Objectives To investigate the clinicopathological characteristics and prognosis of patients with undifferentiated uterine sarcomas (UUS). Methods 29 patients with UUS who were treated at our institution between 2001 and 2020 were analyzed. Results The median age at diagnosis was 52 years (range: 26–70 years). The FIGO 2009 distribution by stage was as follows: stage I, 17 patients (58.6%); stage II, 5 patients (17.2%); stage III, 4 patients (13.8%); and stage IV, 3 patients (10.3%). For 28 patients who underwent surgical treatment, 27 patients (96.4%) underwent total/sub-radical/radical hysterectomy combined bilateral salpingo-oophorectomy, 17 (58.6%) pelvic lymphadenectomy, 7 (24.1%) para-aortic lymphadenectomy and 8 (28.6%) patients underwent omentectomy, as part of the initial surgical treatment. The median follow-up was 23.4 months (range: 4.5–200.2 months). 18 patients (62.1%) died during follow up, and 13 patients (72.2%, 13/18) died within 2 years after diagnosis. Median progression-free survival (mPFS) and overall survival (mOS) for the entire cohort were 15.5 and 27.4 months, respectively. 2-year and 5-year PFS were 40.3% and 26.9%. 2-year and 5-year OS were 54.0% and 36.5%. Stage-specific median PFS and OS were as follows: stage I-II—17.7 and 35.5 months, stage III-IV—6.0 and 6.7 months. Patients with recurrent UUS who underwent cytoreduction surgery associated with an improved overall survival (mOS: 52.9 vs. 17.9 months), but the difference was not statistically significant (P = 0.081). Conclusions UUS are a rare group of tumors with an aggressive behavior and poor outcomes. A majority rapidly develops distant metastases despite surgical resection.